Implementasi Manajemen Berbasis Nilai pada Organisasi Pendidikan - Asep Kurniawan (Menara Tebuireng, 2016)
Value-based management is an approach to management in which managers establish, promote and practice the shared values of the organization. The purpose of shared values are the same values, which is owned by the members of the organization at least has the primary objective. Customer satisfaction as the goal for the organization to provide more services to customers. The values can be implemented in an organization through the performance of a strong leadership. Leaders move on all elements of the organization to jointly build the organization's values. Leaders conduct educational institutional arrangement involving human resources and non-human in a move to achieve educational goals effectively and efficiently. The setup process will involve implementation some management functions by experts in educational management is often referred to as POAC (Planning, Organizing, Actuating, and Controlling)